PHOTO‐SENSITIVE LEAF ROLLING 1 encodes a polygalacturonase that modifies cell wall structure and drought tolerance in rice. Issue 2 (23rd September 2020) - Zhang, Guangheng; Hou, Xin; Wang, Li; Xu, Jing; Chen, Jian; Fu, Xue; Shen, Nianwei; Nian, Jinqiang; Jiang, Zhuanzhuan; Hu, Jiang; Zhu, Li; Rao, Yuchun; et al.
Summary: The biosynthesis and modification of cell wall composition and structure are controlled by hundreds of enzymes and have a direct consequence on plant growth and development. However, the majority of these enzymes has not been functionally characterised. Rice mutants with leaf‐rolling phenotypes were screened in a field. Phenotypic analysis under controlled conditions was performed for the selected mutant and the relevant gene was identified by map‐based cloning. Cell wall composition was analysed by glycome profiling assay. We identified a photo‐sensitive leaf rolling 1 ( psl1 ) mutant with 'napping' (midday depression of photosynthesis) phenotype and reduced growth. The PSL1 gene encodes a cell wall‐localised polygalacturonase (PG), a pectin‐degrading enzyme. psl1 with a 260‐bp deletion in its gene displayed leaf rolling in response to high light intensity and/or low humidity. Biochemical assays revealed PG activity of recombinant PSL1 protein. Significant modifications to cell wall composition in the psl1 mutant compared with the wild‐type plants were identified. Such modifications enhanced drought tolerance of the mutant plants by reducing water loss under osmotic stress and drought conditions. Taken together, PSL1 functions as a PG that modifies cell wall biosynthesis, plant development and drought tolerance in rice.